Miro1 depletion disrupts spatial distribution of mitochondria and leads to oocyte maturation defects - Lee, In-Won; Adhikari, Deepak; Carroll, John (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are dynamic organelles that undergo regulated microtubule- and actin-mediated trafficking to meet local energy and metabolic needs. Mitochondrial trafficking may be particularly critical in large cells such as eggs and early embryos where spindle formation and polar body extrusion occur in specific regions of the cytoplasm. To investigate the role of mitochondrial distribution in oocytes we have targeted the mitochondrial membrane protein, MIRO1, which couples mitochondria to the motor protein-TRAK complex. Oocyte-specific deletion of MIRO1 leads to the formation of large aggregates of mitochondria in perinuclear and cortical compartments. Mitochondria remain capable of long-range trafficking during maturation, indicating redundancy in the mechanisms coupling mitochondria to motor proteins. Polar body extrusion in the absence of MIRO1 was reduced by approximately 20%. In MIRO1-deleted zygotes, mitochondria showed increased accumulation around the pronuclei but this did not affect mitochondrial distribution to daughter blastomeres. In vitro development of parthenogenetic embryos was also reduced, although no differences were found in the fertility of oocyte-specific Miro1 KO mice. These findings demonstrate MIRO1 acts as a mitochondrial adaptor, setting mitochondrial distribution in oocytes and early embryos, and disrupting this process compromises in vitro oocyte maturation and embryo development.